NAPNEE PRACTICES DURING THE PANDEMIC WITH STUDENTS WITH DISABILITIES AT IFMG BETIM CAMPUS (REMUNOM, 2025)
The objective of this study was to analyze whether the practices developed by the Special Educational Needs Service Center (NAPNEE) at IFMG Campus Betim during the COVID-19 pandemic ensured access and retention of students with disabilities in technical courses. Three specific objectives were defined: to verify municipal laws of Betim on disability rights up to 2019, conduct a literature review on the topic, and collect quantitative data on students with disabilities enrolled in technical courses. The research used a quantitative survey of NAPNEE enrollments in 2020, 2021, and 2023. Results indicated no dropout of NAPNEE-supported students during the pandemic, and the number of students assisted by the center increased over the period. It was concluded that adaptive practices were implemented to meet the needs of the students, ensuring their academic continuity.